Zunich neuroectodermal syndrome: migratory ichthyosiform dermatosis, colobomas, and other abnormalities - Tinschert, Sigrid; Anton-Lamprecht, Ingrun; Albrecht-Nebe, Helga; Audring, Heike (Pediatric dermatology, 1996)
Abstract: We report a 21-month-old girl with symptoms consistent with the Zunich neuroectodermal syndrome, an apparently rare condition first described in 1983, Common features of all previously reported patients as well as in this child are characteristic craniofacial dysmorphism, bilateral colobomas of the retina, sparse and fine hair, hearing loss, Ichthyosiform erythroderma, mental retardation, ear anomalies, brachydactyly, and broad second toes. Light microscopic and uttrastructural investigations of the affected skin showed characteristic but nonspecific changes. The structural hair shaft abnormalities as well as the dysplastic nails in our patient have not been described before and are consistent with the previous assumption of an ectodermal dysplasia syndrome.
Gesehen am 27.09.2023